TINJAUAN YURIDIS PASAL 310 UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN TERKAIT PERTANGGUNGJAWABAN HUKUM ORANG TUA TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA KECELAKAAN LALU LINTAS (Studi Putusan Nomor: 41/PID.Sus/2013/PN.SGR) - Ni Kadek Ditya Yulanda Dewi; Made Sugi Hartono; Muhamad Jodi Setianto (Jurnal Ilmu Hukum Sui Generis, 2023)
Children are a mandate and a gift from God Almighty, children are the pillars of hope for the future of the nation, state, community and family as the next generation of the nation. Parents are the first to be responsible for the realization of children's welfare, both spiritually, physically and socially. Parents are obliged to maintain the survival of children and educate them until the child is mature and independent. The purpose of writing this article is to find out criminal responsibility for children as perpetrators of traffic crimes and to find out that parents can be held criminally responsible for traffic crimes committed by their children. The type of research that will be used by researchers is using normative legal research methods, this is intended so that researchers can find out as far as possible what is the measuring tool in discussing this research, so that they can find a point of truth for the purpose of this research. The approach used is in the form of a statutory regulation approach, literature and a case approach. The conclusions that can be drawn from this study, the authors describe in the form of criminal responsibility for children as perpetrators of traffic crimes require the fulfillment of the conditions for criminal responsibility for a child, but should still pay attention to the psychological development of the child's soul. This becomes the author's input regarding the affirmation of the child's responsibility model in traffic crimes.